A Prospective Evaluation of Opioid Utilization After Benign Gynecological Surgery [01H]. (May 2020) - Wright, Danielle; Soper, David; Korte, Jeffrey
Abstract : INTRODUCTION: Opioids provide an effective means to controlling postoperative pain. However, this medicine is overprescribed and the lack of prescribing guidelines contribute to this issue. As-Sanie et al (2007) reported gynecologists prescribed twice the amount of opioids than the average patient used after hysterectomy. Our goal, for this study, was to define the pattern of opioid utilization after benign gynecologic surgery. METHODS: This is a prospective cohort study. Women were deemed eligible for enrollment if they underwent hysteroscopy, laparoscopy, and hysterectomy. Patients were excluded from the study if there was suspicion for malignancy. Following discharge, a 17-question phone survey was completed 14 days post op to assess opioid consumption. RESULTS: A total of 109 women participated in the survey. Over all procedures, the median proportion of opioids used was 40% (IQR 13-100%) with the difference between the median MME (morphine milligram equivalent) prescribed and used being statistically significant for all procedures. CONCLUSION: This study highlights the practice of overprescribing, which should be a target area for improvement for benign gynecologists. We recommend using each procedure's IQR for prescribing guidance. Adjustments in quantity can be made based on patient history and collaborative decision making.